Influence of social factors, clinical characteristics and comormidities on the health related quality of life in patients with tension type headaches - L. R. Akhmadeyeva; E. N. Zakirova; V. A. Voevodin; R. V. Magzhanov (Бюллетень сибирской медицины)
Here we present the results of our study of the influence of clinical and social parameters as well as co-morbidities (as anxiety, depression, sleep disturbances) on the health related quality of life of 95patients with the most often met primary cephalgias — tension type headache. We used MOS-SF36 (Medical Outcomes Study Short Form-36) as the main instrument to measure health related quality of life. Significant influence of anxiety and depression on the quality of life in patients with both frequent episodic and chronic tension type headache was reported. Anxiety in these patients was mostly associated with psychic health, general health and vitality. In patients with chronic tension type headaches depression was associated with physical functioning; in those with frequent episodic tension type headaches — with social functioning and role functioning due to emotional sate.